Searching for charged Higgs bosons via e+e− → H+H− → c̄bc̄b at linear colliders - Hou, Wei-Shu; Jain, Rishabh; Modak, Tanmoy (Journal of high energy physics, 2022)
We study a search for the charged Higgs boson via e+e− → H+H− → $$ \overline{c}b\overline{c}b $$at the 500 GeV ILC. In a general two Higgs doublet model without Z2 symmetry, extra Yukawa couplings ρtt and ρtc can drive baryogenesis, but searches at the HL-LHC may still go empty-handed if the couplings are relatively weak. Taking $$ {m}_{H^{+}} $$≃ mH ≃ mA ≃ 200 GeV, with ρtt, ρtc ∼ 0.1 and no h(125)-H mixing, H+ → $$ c\overline{b} $$decay is dominant, and the $$ \overline{c}b\overline{c}b $$final state is likely overwhelmed by QCD background at the LHC. We show that the electroweak production of H+H− at the ILC is discoverable with integrated luminosity of 1 ab−1. Furthermore, we show that $$ {m}_{H^{+}} $$can be extracted by requiring the two pairs of b and light jets be roughly equal in mass, without assuming the mass value. Thus, ILC can probe low mass Higgs bosons in multijet final states to complement HL-LHC in the future.
Gesehen am 09.11.2022
Im Titel ist "+" und "-" hochgestellt